ESTIMATING AND ACCOUNTING FOR UNCERTAINTY - BRAGĂ FILOFTEIA VIORICA; NĂFTĂNĂILĂ ALINA CRISTINA; SOARE JANINA; DARIE CASIANA MARIA (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie, 2019)
In this paper we will outline the main aspects by which uncertainty can be reflected in accounting through provisions for risks and expenses. The management of a company is directly involved in the production of accounting information. Therefore, they need to be careful, responsible and prudent when presenting accounting data. In the second part we analysed the prudence in evaluating and reflecting the uncertainty by analysing the types of provisions for risks and expenses constituted and reflected in the financial statements prepared for 31.12.2018 of 40 companies listed on the AeRO market of BVB whose shares will be traded on the basis of the continuous trading model starting July 12, 2019.